The present and the future: Strategic partnering to support MSLs (International Journal of Scientific Research and Management (IJSRM), 2017)
A study published in 2012 analyzed more than three dozen drug and device companies’ Medical Science Liaison (MSL) operations around the world. The study revealed that the top 20 pharmaceutical organizations invest between 10 million and 48 million to deploy MSLs in the US, Europe and Asia.